Is AUD the same for everyone? The different typologies of AUD patients - Otto-Michael Lesch; Henriette Walter (Nutrimentum et Curae)
Alcohol dependence and related disabilities are a large burden for the population. Problems in families, working places and severe medical symptoms are often caused by alcoholism. Most of these patients never reach a specialized, high-quality treatment program. They get no specific withdrawal treatment, no specific psychosocial help, and only 3-5% get anticraving medications.